2021
DOI: 10.3389/fcvm.2021.705282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined High-Protein Diet and Exercise Intervention on Cardiometabolic Health in Middle-Aged Obese Adults: A Randomized Controlled Trial

Abstract: Background: Obesity is the main risk factor of cardiovascular diseases (CVD) and metabolic diseases. The middle-aged population is the age group with the highest prevalence of obesity. Thus, improving cardiometabolic health is important to prevent CVD and metabolic diseases in middle-aged obese adults. The aim of this study was to examine the effects of exercise alone or in combination with a high-protein diet on markers of cardiometabolic health in middle-aged adults with obesity.Methods: Sixty-nine middle-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Over the last years, HP diets have been suggested as healthier alternatives that contribute to achieving sustained weight loss or improving muscle mass, while simultaneously preserving good cardiovascular and skeletomuscular health. However, available evidence from cohort studies seems quite controversial, with the majority of studies showing a positive impact of HP diets on cardiometabolic risk reduction, both in apparently healthy populations and in people at a high risk of, or with already established, CVD [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. On the other hand, some studies demonstrated a negative impact of HP diets on cardiometabolic profile [ 18 , 19 ] and regarding hard cardiovascular and renal outcomes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last years, HP diets have been suggested as healthier alternatives that contribute to achieving sustained weight loss or improving muscle mass, while simultaneously preserving good cardiovascular and skeletomuscular health. However, available evidence from cohort studies seems quite controversial, with the majority of studies showing a positive impact of HP diets on cardiometabolic risk reduction, both in apparently healthy populations and in people at a high risk of, or with already established, CVD [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. On the other hand, some studies demonstrated a negative impact of HP diets on cardiometabolic profile [ 18 , 19 ] and regarding hard cardiovascular and renal outcomes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…HP diets, with or without the restriction of carbohydrate intake, have gained increased popularity because they are being promoted as a means of losing weight, increasing muscle mass and strength, preserving a functional skeletomuscular system, improving cardiometabolic parameters, and even cardiovascular outcomes, both in apparently healthy populations and in people at high risk of, or with already established, CVD [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. On the other hand, there are studies that appear to associate increased protein consumption with unfavorable metabolic profiles, development, or deterioration of type 2 diabetes mellitus (T2DM) [ 18 , 19 ], worse cardiovascular and renal outcomes [ 20 , 21 , 22 ], and even with higher all-cause and cause-specific mortality, focusing on cancer and CVD [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation